Landasan Filosofis Postmodern dalam Pengembangan Model Pembelajaran Kontemporer - Fathurrahman Fathurrahman; Sariyatun Sariyatun; Heri Susanto (Jurnal Studi Guru dan Pembelajaran, 2025)
Contemporary education faces complex challenges in responding to increasingly diverse social realities, where traditional modern paradigms emphasizing objectivity, linearity, and single rationality are beginning to be questioned for their effectiveness. The urgency of educational transformation is becoming increasingly pressing in light of developments in digital technology, globalization, and the post-truth era, which demand learning approaches that are more adaptive, inclusive, and responsive to the complexities of the times. This study aims to explore the postmodern philosophical foundations as a basis for developing innovative learning models that reject universal rationality and accommodate plurality of perspectives. The research uses a literature review approach by analyzing twelve relevant scientific articles published between 2020 and 2025 from accredited national and international journals. The selection process includes articles that have undergone peer review, are available in full text, and are relevant to postmodern philosophy, learning innovation, and 21st-century education. Data analysis was conducted through in-depth reading, thematic identification, comparison, and synthesis of information. The findings reveal that postmodern educational philosophy emphasizes pluralism, criticism of grand narratives, and curriculum decentralization as the foundation for more inclusive learning. The main themes identified include paradigmatic transformation requiring decentralization of pedagogical processes, integration of humanistic technology through adaptive digital learning, innovative methodologies emphasizing subjectivity and creativity, adaptive strategies responsive to technological changes, and development of authentic identity through intrinsically motivated and reflective learning. The research concludes that the development of contemporary learning models must integrate philosophical, technological, methodological, strategic, and psychological aspects within a holistic framework that transforms education from rigid knowledge transfer into a space for the liberation of meaning that values diversity and context.